LJSS 2021
DOI: 10.31039/ljss.2021.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teachers’ Professionalism Through Blended-Based Training in Indonesia's Remote Area

Abstract: Blended-based training is a best alternative choice for equalization of training in Indonesia's district area in the Covid-19 pandemic era considering the low competency of teachers in Indonesia at this time. This research was applied on improving the teachers' professionalism in Indonesia's remote area in order to act their main roles on preparing the learning administration. The research method used was experimental research by one-group pre-test and post-test design. Research subject were from normative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Teacher competence could be improved through several efforts, one of the proven efforts was through training. This was in line with teachers (Slameto et al, 2017), (Qomariah, 2020), and (Pohan et al, 2021) Particularly, the trainees were trained to improve skills in using online learning media, the ability to provide reinforcement and the ability to implement relevant learning methods.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Teacher competence could be improved through several efforts, one of the proven efforts was through training. This was in line with teachers (Slameto et al, 2017), (Qomariah, 2020), and (Pohan et al, 2021) Particularly, the trainees were trained to improve skills in using online learning media, the ability to provide reinforcement and the ability to implement relevant learning methods.…”
Section: Discussionmentioning
confidence: 53%
“…The results of previous empirical studies showed that the online and offline training have significant effect on increasing teacher competence. The results of the research by Pohan, et al (2021) showed that online training has successfully to improve the competence of teachers in the outer regions of Indonesia. Teachers could attend training flexibly without leaving the workplace and without high payment.…”
Section: Online Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kompetensi guru juga dapat ditingkatkan melalui pelatihan secara rutin. Hasil studi empiris menunjukkan bahwa mengikuti pelatihan dapat meningkatkan pengetahuan guru, kompetensi guru, dan hasil kinerja guru (Slameto et al, 2017), (Qomariah, 2020, dan (Pohan et al, 2021).…”
Section: Kajian Pustaka Kompetensi Guruunclassified
“…Hasil studi empiris terdahulu menunjukkan bahwa pelatihan online maupun offline berpengaruh signifikan terhadap peningkatan kompetensi guru. Hasil penelitian Pohan et al, (2021) menunjukkan bahwa pelatihan online dapat meningkatkan kompetensi guru di daerah terluar Indonesia. Guru dapat mengikuti pelatihan secara fleksibel tanpa meninggalkan tempat kerja.…”
Section: Pelatihan Secara Onlineunclassified